2014
DOI: 10.1007/s00580-014-1905-y
|View full text |Cite
|
Sign up to set email alerts
|

Hematological variables of the Pêga donkey (Equus asinus) breed: influence of age and sex

Abstract: Appropriate hematological reference intervals mitigate the risk of unnecessary investigations and failures on disease diagnosis. Species, breed, environment, handling, and physiologic stage could influence hematological variables. In this context, there is a lack of hematological reference intervals for Pêga donkeys, an important Brazilian asinine breed. This study aimed to establish hematological reference values for Pêga donkeys and determine the influence of age and sex on these variables. The complete bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
4
9
1
Order By: Relevance
“…The EOS in our study tended to increase with age, which is in agreement with other studies (Zinkl et al 1990;Girardi et al 2014) but at odds with Folch et al (1997) who reported a decrease of this variable with aging. We can presume that this increase in EOS may be attributed to a higher parasitic burden with age or progressive contact with allergen antigens.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The EOS in our study tended to increase with age, which is in agreement with other studies (Zinkl et al 1990;Girardi et al 2014) but at odds with Folch et al (1997) who reported a decrease of this variable with aging. We can presume that this increase in EOS may be attributed to a higher parasitic burden with age or progressive contact with allergen antigens.…”
Section: Discussionsupporting
confidence: 93%
“…On the one hand, many previous studies (mentioned above) describe varying indices for different sexes and ages in a population of donkeys (Folch at al. 1997;Jordana et al 1998;Mori et al 2003Mori et al , 2004Girardi et al 2013Girardi et al , 2014. On other hand, in the study of French and Patrick (1995) based on a population of approximately 4,000 donkeys, no differences in biochemical indices in relation to age and sex were found.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This in turn requires the understanding of haematological profiles of an, apparently, healthy animal, whose physiological parameters provide invaluable information regarding the health status of the animal (Kral and Suchy 2000 ; Mori et al 2003 , 2004 ; Cetin et al 2009 ). Inspite of the clinical significance, correct haematological interpretation and analysis are sometimes difficult because many factors considerably influence the haematological parameters in goats, pigs, rabbits, camels, cattle, horses and donkeys, including age (McFarlane et al 2001 ; Caldin et al 2005 ; Gurgoze and Icen 2010 ; Melo et al 2013 ; Padalino et al 2014 ; Girardi et al 2014 ;), sex (Cetin et al 2009 ; Mirzadeh et al 2010 ; Uluisik et al 2013 ; Girardi et al 2013 , 2014 ), breed (Tibbo et al 2004 ; Lacerda et al 2006 ; Orozco et al 2007 ; Šimpraga et al 2013 ), seasons (Dmoch et al 2008 ; Adenkola et al 2011 ; Mirzadeh et al 2010 ; Abdelatif and Alameen 2012 ; Babeker et al 2013 ; Šimpraga et al 2013 ), diet (Ekenyem and Madubruke 2000 ; Iyayi 2001 ; Kumar et al 2005 ), health status and sub-clinical disease (Rose and Hodgson 1994 ; Petrov et al 2011 ; Kalai et al 2012 ) work or exercise (Piccione et al 2001 ; Zobba et al 2011 ; Kedzierski et al 2009 ; Miranda et al 2011 ) and pregnancy (Harvey et al 1994 ; Orozco et al 2007 ; Satué et al 2010a , b ; Farooq et al 2011 ; Okonkwo et al 2011 ; Aoki and Ishii 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Brazilian Association of Pega Donkey Breeders (ABCJ Pega) has approximately 2000 members and about 20 000 mules and donkeys registered (Canisso and McDonnell 2010). However, only a limited amount of research has been performed on the haematological and serum biochemical variables of this breed (Campos et al 1968;Girardi et al 2014;Girardi et al 2015;Girardi et al 2016).…”
mentioning
confidence: 99%